Credit policy and credit appraisal of canara bank using ratio analysis - Varathan, Sathya; Kalyanasundaram, Priya; Tamilenthi, S (International Multidisciplinary Research Journal, 2012)
Credit appraisal is an important activity carried out by the credit department of the bank to determine whether to accept or reject the proposal for finance. The article deals in banking such as working capital and its management, working capital methods of assessment, compilation of credit reports. The study included working capital, working capital cycle and working capital management of Canara Bank. The methods that are used by the banks in order to calculate the loan limits are Turnover method, MBPF system and Cash budget system. The financial statements were taken for a period of five years from 1st April 2007 to 31st March 2012. The Profit and loss account and Balance sheet were analyzed. The firm’s financial performance is analyzed through ratio analyses. The study shows Canara bank has sound system for credit appraisal and the bank has good parameters to appraise the project.